The Influence of Land Area on Rice Farmers' Income in SP9, Jabamaru Village, Tanah Miring District, Merauke Regency - Susiani Susiani; Susana Santu; Asril Putra Siwa (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
This study aims to determine the effect of land size on the income of rice farmers in SP9 Jabamaru Village, Tanah Miring District, Merauke Regency. The research is motivated by the significant role of agriculture in Indonesia's economy, especially in areas where most residents are farmers. Land size is one of the critical factors influencing the success of farming activities, as it affects production capacity and directly impacts farmers' income. This quantitative research uses a survey method involving 53 rice farmers as a sample from a total population of 214 farmers. Data collection techniques include observation, interviews, and questionnaires. The data were analyzed using simple linear regression with IBM SPSS version 25. The results show that land size has a positive and significant effect on farmers' income. The regression coefficient of 9,585,807.223 indicates that each additional hectare of land significantly increases income. A significance value of 0.000 (smaller than 0.05) and a t-statistic of 16.262 (greater than t-table 1.675) support this result. Therefore, the hypothesis that land size affects farmers' income is accepted. The study recommends that farmers improve land management efficiency and optimize land use to enhance their income levels.